2000
DOI: 10.1002/1096-8628(20000703)93:1<40::aid-ajmg7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor fluorescence in situ hybridization analysis of meiotic chromosome segregation in a 47,XYY male and a review of the literature

Abstract: The frequencies of aneuploid and diploid sperm were determined in a 47,XYY male using multi-color fluorescence in situ hybridization (FISH) analysis, and compared with those from 10 control donors. A total of 30,078 sperm from the patient was scored, 15,044 by two-color FISH for chromosomes 13 and 21, and 15,034 by three-color FISH for the sex chromosomes using chromosome 1 as an internal autosomal control for diploidy and lack of hybridization. The frequencies of X-bearing (49.73%) and Y-bearing sperm (49.46%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 33 publications
(46 reference statements)
5
25
0
3
Order By: Relevance
“…Results from this larger sperm sample suggested that the additional chromosome is eliminated during spermatogenesis in the majority of cells, but that there may be a small but significant increase in the frequency of aneuploid sperm in these men. A recent study of another 47,XYY male in our laboratory yielded similar results, with a small but significant increase in the frequency of sex chromosomal aneuploidy (0.6%; Shi and Martin 2000). Twelve other 47,XYY males have been studied by FISH analysis with a frequency of sex chromosomal aneuploidy ranging from 0.3% to 15% (reviewed by Shi and Martin 2000).…”
Section: Introductionsupporting
confidence: 70%
“…Results from this larger sperm sample suggested that the additional chromosome is eliminated during spermatogenesis in the majority of cells, but that there may be a small but significant increase in the frequency of aneuploid sperm in these men. A recent study of another 47,XYY male in our laboratory yielded similar results, with a small but significant increase in the frequency of sex chromosomal aneuploidy (0.6%; Shi and Martin 2000). Twelve other 47,XYY males have been studied by FISH analysis with a frequency of sex chromosomal aneuploidy ranging from 0.3% to 15% (reviewed by Shi and Martin 2000).…”
Section: Introductionsupporting
confidence: 70%
“…However, a high incidence of sex chromosomal aneuploidies has been observed repeatedly in sperm samples also when the patient´s sperm sample had a low morphological quality and the karyotype in lymphocytes was normal [27][28][29][30][31][32][33][34]. This is because paternal nondisjunction of the meiotic chromosomes includes much more the sex chromosomes (X and Y) than the autosomes, whereas aneuploidies of chromosome 13, 16, 18, 21 occur more frequently by maternal errors during the first and second meiotic division of the maturing oocyte [35].…”
Section: Fig (2)mentioning
confidence: 98%
“…However, all chromosome abnormalities are generally counter-selected by the meiotic segregation mechanisms [26], and translocation chromosomes are expected with a variable frequency in the postmeiotic germ cells. Robertsonian translocation chromosomes were found with a frequency between 3-27% for an unbalanced karyotype in postmeiotic germ cells by FISH and karyotype sperm analyses [32]. Therefore, although there is a general risk for an unbalanced karyotype in the patientsó ffspring, its individual frequency can only be identified by FISH in the germ cells of the patient directly.…”
Section: Fig (2)mentioning
confidence: 99%
“…Klinefelter men and mice are usually sterile with a block occurring before meiosis, during the early spermatogonial divisions (Ferguson-Smith 1959;Mroz et al 1999;Lue et al 2001). For Double Y syndrome men, the reproductive outlook varies; the extra Y chromosome is often lost during the early spermatogonial stages and this generates XY (euploid) cell lines that can complete spermatogenesis and support fertility (Chandley 1997;Shi and Martin 2000). In XYY men and mice in which XY cell lines do not arise, infertility results, with germ cell losses occurring during pachytene and the meiotic divisions (Speed et al 1991;Solari and Rey Valzacchi 1997;Mahadevaiah et al 2000;Rodriguez et al 2000).…”
Section: Overview Of Sex Chromosome Infertilitymentioning
confidence: 99%